Hubungan Aktivitas Fisik Sedenter dengan Siklus Menstruasi Mahasiswi Fakultas Kedokteran UHAMKA - Hanifah, Anisa Nabila Hanifah; Sukarya, Wawang Setiawan (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2023)
High intensity physical activity affects Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) while low physical activity that leads to less body movement affects oxidative energy reserves. This study aims to determine the relationship between sedentary physical activity and the menstrual cycle of students of the Faculty of Medicine, Universitas Muhammadiyah Prof. Dr. HAMKA (UHAMKA). The research design was an observational analytic survey with a cross sectional approach. The sample size was determined by the Slovin formula, which was 92 subjects. The results showed that most of the female students (95.65%) with sedentary physical activity, and female students with abnormal menstrual cycle disorders (polymenorrhea) were 31.52% oligomenorrhea 11.96%, hypomenorrhea 64.13%, while hypermenorrhea was only 3.27%. There is no significant relationship between the level of sedentary physical activity with menstrual cycle disorders.